PERSEPSI PENDIDIK VOKASI ATAS ATRIBUT-ATRIBUT EMPLOYABILITYSKILLS YANG DIBUTUHKAN DUNIA KERJA ERA REVOLUSI INDUSTRI 4.0 - Suarta, I Made; Suwintana, I Ketut; Sudhana, I G P Fajar Pranadi; Hariyanti, Ni Kadek Dessy (UI Scholars Hub, 2020)
The aim of study was to examine the perceptions of higher vocational educators about the importance level of employability skills attributes that needed by higher vocational education graduates in entering the workforce in the era of industrial revolution 4.0. The study was conducted by survey method, using a questionnaire. Respondents were selected by purposive sampling from state and public polytechnic vocational accounting educators. The research instruments were arranged based on a hypothetical model of employability skills which included generic skills and personal attributes. The generic skills group consists of 45 items and personal attributes consists of 20 items. The research instrument was arranged in the form of closed questions using five point Likert scale, ranging from not important to very important. Data were analyzed by descriptive statistics, namely mean scores, standard deviations, and graphics. The average score is sorted from high to low, indicating the importance level of employability skills according to higher vocational educator perceptions. Communication skills, self-management skills, teamwork skills, and learning skills are generic skills groups with a high importance level perceived by higher vocational educators. Educators also place honesty, integrity, work ethics, accuracy, and have good personalities as personal attributes with a high importance level that must be possessed by higher vocational graduates. The implication of this finding is the need to revitalize higher vocational education curriculum, which are not solely focused on mastering the knowledge and technical skills in specific field, but also able to develop the attributes of employability skill students.